2013
DOI: 10.1111/jgs.12400
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults Recently Discharged from the Hospital: Effect of Aerobic Interval Exercise on Health‐Related Quality of Life, Physical Fitness, and Physical Activity

Abstract: High-intensity aerobic interval exercise (HIA) participants significantly improved their physical fitness. Both groups increased their HRQOL and physical activity. The findings suggest that exercise therapy should be incorporated as a part of the treatment for older people at risk for functional decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(95 citation statements)
references
References 31 publications
6
83
1
5
Order By: Relevance
“…Moreover, adults with multiple chronic illnesses appeared to receive similar benefit from recommended levels of PA. These results are consistent with randomized controlled trials that have shown increases in PA with simultaneous increases in HRQOL [19,20,21,22]. These findings are further supported by studies that have shown increased HRQOL in physically active participants with chronic diseases [23][24][25][26][27][28][29].…”
Section: Odds Ratios (Ors)supporting
confidence: 81%
“…Moreover, adults with multiple chronic illnesses appeared to receive similar benefit from recommended levels of PA. These results are consistent with randomized controlled trials that have shown increases in PA with simultaneous increases in HRQOL [19,20,21,22]. These findings are further supported by studies that have shown increased HRQOL in physically active participants with chronic diseases [23][24][25][26][27][28][29].…”
Section: Odds Ratios (Ors)supporting
confidence: 81%
“…Another study found that patients with generalized weakness had an increase change of admit and return within 30 days [7]. It may be that patients with generalized weakness and fatigue need to be assessed for additional rehabilitation or home health treatments [8][9][10].…”
Section: Discussionmentioning
confidence: 96%
“…Although highintensity exercise training programs can bring about clear health benefits for older adults recently discharged from the hospital (Brovold, Skelton, & Bergland, 2013), intensity does not need to be high to reduce the risk of developing chronic cardiovascular or metabolic diseases (de Vries et al, 2012). Safety is more important.…”
Section: Discussionmentioning
confidence: 99%